Assessment of the perception of self-care among adolescents in Andalusia - Rodríguez Martínez, Antonio (Enfermería Cuidándote, 2026)
Introduction: Given the growing concern surrounding risk behaviors in adolescence and the limited exploration of self-care from a multidimensional perspective, this study is justified by the need to analyze this phenomenon in a comprehensive manner.Objectives. The overall objective was to assess the level of self-care among young people in Andalusia and analyze its variations following the COVID-19 pandemic. Specifically, we sought to examine the relationship between self-care and the risk of eating disorders (EDs) and negative exercise addiction (NEA).Methodology. A mixed research design was used. The quantitative phase consisted of a cross-sectional study with a sample of 1,018 adolescents to validate the Youth Self-Care Practice and Management questionnaire. The qualitative phase was based on interviews with teachers to gain insight into the social and educational context.Results. The findings revealed a strong interrelationship between the self-care dimensions, confirming family support as a significant protective factor. Regression analysis identified that greater frequency of physical activity and self-care management were significant predictors of increased ED risk. For NEA risk, only physical activity was found to be a significant predictor.Discussion and Conclusion. The study validates the PGJ questionnaire as an effective tool for early risk detection. The findings conclude that it is essential to implement a comprehensive approach that actively involves families and educational centers to effectively promote healthy habits and well-being among adolescents.
Keywords: Adolescent Health; Adolescents; Compulsive Exercise; Family Relations; Feeding and Eating Disorders; Health Risk Behaviors; mental health; Self Care; Social Support